Microwave multimeter for the high level power control - Volcov, V. M.; Bortnik, S. A.; Indina, O. B.; Ogui, A. V. (My University, 1998)
This report is devoted to the problem of designing and constructing the built-in multiprobe analyzer of microwave signals and fider parameters. There has been considered the structure of a universal passing power sensor based on absorbing wall principle and used for high level passing power measurement
Keywords: microwave multimeter; sensor; absorbing wall; built-in analyzer; passing power measurement; structure; high leve power